Beware of Greeks Bearing Gifts?: Changing relations and Responses to and from Greek Settlers in Western Australia - Yiannakis, John (Department of the Premier and Cabinet, Office of Multicultural Interests, 2005)
The recent commercial success in Australia of the film “My Big Fat Greek Wedding”, not only suggests an ability by English speaking Greeks to parody themselves and the experiences of their forebears, but an acceptance of the Greek stereotype and an embrace of the Greek presence by the broader Australian community. However, such an acceptance has not always been the case, and it still might not be as harmonious a relationship as large attendances at the film may imply. The reality of the Greek experience and contribution to Australia is quite different to the congenial and embracing portrayal of the film. For much of the twentieth century Greeks were “foreigners”, labelled and lumped together with other Southern Europeans as “dings and dagos”. Yet, despite such vitriol, Western Australia would afford Greek settlers and their descendants opportunities to better themselves and to contribute to the development of the state, while being able to maintain aspects of their cultural heritage.